Rice straw incorporation and Azolla application improves agronomic nitrogen-use-efficiency and rice grain yields in paddy fields - Marzouk, Said H.; Semoka, Johnson M.; Amuri, Nyambilila A.; Tindwa, Hamisi J. (Frontiers in Soil Science, 2024)
In paddy soils, excessive application of N fertilizer often results in substantial N losses due to low N utilization efficiency. However, this condition can be mitigated by enhancing soil organic carbon content. Two-year field experiment was carried out at Mkula Irrigation Scheme in Kilombero Valley, Tanzania with the aim of investigating the impact of Azolla, rice straw incorporation and reduced levels of nitrogen input from NPKS-containing fertilizers on N use efficiency, soil chemical properties and rice grain yield. Assuming that this technology will introduce a novel perspective to the research, shedding light on alternative and potentially more sustainable methods for nitrogen management in paddy soils, it will be particularly relevant in sub-Saharan Africa, where the annual cost of chemical fertilizers is expected to continue rising. The treatments involved absolute control, half dose N (50 kg N ha-1), full dose N (100 kg N ha-1), and combination of these N doses with PKS, dry Azolla (3.4 t ha-1) and rice straw (6.9 t ha-1) through omission approach. The soil of the experimental area was sandy clay loam in texture, very strongly acid (pH 4.8), normal electrical conductivity (0.06 dS m-1), low amounts of recorded organic carbon (1.35%), total nitrogen (0.33%), 0.68 mg kg−1 available P, exchangeable potassium (0.15 cmol(+) kg−1), calcium (0.19 mg kg−1) and sodium percentage (3.75%), with very low cation exchange capacity (1.6 cmol(+) kg−1). The results showed that combination of Azolla, rice straw +100 kg N ha-1 + 30 kg P ha-1 + 30 kg K ha-1 + 20 kg S ha-1 resulted in higher rice grain yield, nitrogen uptake and agronomic efficiency of N. Azolla, being an effective biofertilizer, significantly contributes to nitrogen fixation and soil enrichment. Interestingly, this study demonstrates that co-application of Azolla, rice straw, and 50% reduced N is effective for achieving high rice yields, minimizing over-dependence on chemical N fertilizer, sustainable agricultural development, and environmental conservation.